2005
DOI: 10.1152/ajpendo.00444.2004
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle myofibrillar protein metabolism in heart failure: relationship to immune activation and functional capacity

Abstract: LeWinter. Skeletal muscle myofibrillar protein metabolism in heart failure: relationship to immune activation and functional capacity. Am J Physiol Endocrinol Metab 288: E685-E692, 2005. First published November 23, 2004; doi:10.1152/ajpendo.00444.2004.-Chronic heart failure is characterized by changes in skeletal muscle that contribute to physical disability. Most studies to date have investigated defects in skeletal muscle oxidative capacity. In contrast, less is known about how heart failure affects myofibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
53
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 35 publications
10
53
2
Order By: Relevance
“…Therefore, the questions remains as to what causes deficits in whole muscle function in heart failure patients. Recent studies from our laboratory have shown that heart failure promotes a reduction in skeletal muscle MHC protein content (31), presumably via downregulation of MHC transcription (27). As we clearly demonstrate in Fig.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Therefore, the questions remains as to what causes deficits in whole muscle function in heart failure patients. Recent studies from our laboratory have shown that heart failure promotes a reduction in skeletal muscle MHC protein content (31), presumably via downregulation of MHC transcription (27). As we clearly demonstrate in Fig.…”
Section: Discussionsupporting
confidence: 68%
“…Although many functional differences between fiber types have been ascribed to myosin composition (1,15), variation in the composition of thin-filament proteins, such as troponin C, I, and T isoforms (20,22,23), could also contribute. This point is particularly relevant to our results since our laboratory (31) and others (36) have shown alterations in fiber-type distribution in CHF, with a shift toward a more fast-twitch phenotype. To directly test whether variation in fiber type affects thinfilament function, we isolated native thin filaments from rat EDL and soleus muscles [composed primarily of fast-twitch and slow-twitch fibers, respectively (32)] and characterized their function using the in vitro motility assay.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations